Influence of television programs genre on violent behaviour among young children - Nazari, Mohammad Reza; Hassan, Md. Salleh; Osman, Mohd Nizam; Yasin, Megat Al-Imran; Parhizkar, Saadat (Sciencedomain International, 2013)
The purpose of this study was to examine the relationship between television program genre and aggression behaviour in primary school students. The results of the survey revealed a significant relationship between watching movies with action genre and aggression level among students (p<0.05). Finding indicated that there was no difference between mean of aggression level among children who interested in particular type of TV programs, except animation which showed a significant difference (p<0.05). In conclusion current study provides additional evidence to support that content of television programs particularly its genre is very important in shaping the children behavior. As a new perspective, focus on genre as an important element in producing of television programs could be helpful for authorities.